Evaluation of methyl jasmonate as elicitor in the production of cycloartane saponins in Astragalus aitosensis in vitro root cultures - Preslav Enchev; Yancho Zarev; Iliana Ionkova (Pharmacia)
Methyl jasmonate (MeJA) treatment is known to increase the levels of plant secondary metabolites. The significant medicinal benefits of cycloartane type saponins, including immune modulation, antiviral properties, and antitumor activity, drive high global demand, making sustainable production methods economically, medically, and ecologically important. In this study the effect of MeJA as an elicitor for promoting higher accumulation of cycloartane saponins – astragaloside I, II and IV was evaluated. The experiment was conducted using biotechnological approaches for sustainable production using in vitro root cultures of the endemic plant species Astragalus aitosensis, which is known to produce rare cycloartane saponins. LC-HRESI-MS analysis was used to identify and quantify compounds. The content of astragaloside I increased significantly by 68% (118 ng/mg DW) compared to control group (70 ng/mg DW). Astragaloside II was found with 1.5 points increased amount (473 ng/mg DW), compared to control (331 ng/mg DW) and astragaloside IV production was also improved. The highest cost-efficacy concentration of the elicitor for all tested astragalosides was observed at 50 µL MeJA.